Prevalence of urinary incontinence and its association with the body mass index (BMI) among pregnant women in Ternate Island - Adi Ariffianto; Ova Emilia; Edi Patmini Siswanti; Abdul Wahab (Universitas Gadjah Mada, 2019)
Urinary incontinence, a condition where a patient cannot withhold urinating, can cause health, social and psychological problems. This condition is not life threatening but can affect their quality of life due to the difficulties of treatment in the psychological and social problems. Even though this disorder is common in pregnancy, the exact cause is still unknown. Many researchers assert that urinary incontinence is due to multifactorial causes. This study aimed to determine the prevalence of urinary incontinence in pregnant women and its relationship with body mass index (BMI). A cross sectional study involving 224 pregnant women in the primary health centers on Ternate Island was conducted using the Questionnaire for Urinary Incontinence Diagnosis (QUID). Respondents with a history of urinary incontinence without pregnancy or positive urinary tract infection diagnosis were excluded from this study. Data were gathered through interviews and physical examinations. The total prevalence of urinary incontinence was 28.6%. Urge incontinence (39.0%) was the most common type followed by mixed (37.5%) and the least common was stress incontinence (23.4%). There was a significantly association between urinary incontinence and maternal BMI (p=0.045). Urinary incontinence occured as much as 2.167 (95% CI: 1.008 - 4.656) times greater in pregnant women with obesity than those who had an ideal BMI. In conclusion, urge incontinence is the most common type of urinary incontinence. There is a significant correlation between urinary incontinence and the BMI of pregnant women, especially in obese women.